1999
DOI: 10.2172/329496
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of high explosives on granular activated carbon [GAC]: Enhanced desorption of high explosives from GAC -- Batch studies

Abstract: Adsorption to GAC is an effective method for removing high explosives (HE) compounds from water, but no permanent treatment is achieved. Bioregeneration, which treats adsorbed contaminants by desorption and biodegradation, is being developed as a method for reducing GAC usage rates and permanently degrading RDX and HMX. Because desorption is often the limiting mass transfer mechanism in bioregeneration systems, several methods for increasing the rate and extent of desorption of RDX and HMX are being studied. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In baseline desorption tests with buffered water, 57.7% (76.5 mg) of the initially adsorbed RDX was desorbed by 36 500 BV of buffered water over 2.9 days. The HSDM predictions matched the experimental data very well (model results not shown; Morley, 2000 ), providing further evidence that RDX reversibly adsorbs to GAC. Results of desorption with water are included in Figures 2 and 3 for comparison with other enhanced desorption methods.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In baseline desorption tests with buffered water, 57.7% (76.5 mg) of the initially adsorbed RDX was desorbed by 36 500 BV of buffered water over 2.9 days. The HSDM predictions matched the experimental data very well (model results not shown; Morley, 2000 ), providing further evidence that RDX reversibly adsorbs to GAC. Results of desorption with water are included in Figures 2 and 3 for comparison with other enhanced desorption methods.…”
Section: Resultssupporting
confidence: 63%
“…For all simulations related to this research, 12 axial and 3 radial collocation points were used. Further details of the algorithms and computer solution methods are presented by Crittenden et al (1986) and Friedman (1984) , and additional details of the modeling are included in Morley (2000) .…”
Section: Methodsmentioning
confidence: 99%
“…The adsorption technique has been extensively employed in the removal of hazardous pollutants and is acknowledged to be a very promising approach owing to its high selectivity and cost-efficacy [ 53 , 54 , 55 , 56 , 57 ]. The commercially available and synthesized activated carbon-based adsorption of toxic pollutants has been reported by many researchers [ 58 , 59 ]. Various low-cost materials have also been examined to develop efficient activated carbon [ 58 ].…”
Section: Hmx Remediation Approachesmentioning
confidence: 99%
“…Different types of GACs were selected for this study and among all, the Calgon F400 sample was found to be very effective in HMX removal. Explosive-loaded GAC was regenerated by using bio-regeneration where explosive-loaded GAC was degraded in a bioreactor [ 59 ]. It was noted that HMX reduced from 0.6 mg/L to 0.4 mg/L in 4 days.…”
Section: Hmx Remediation Approachesmentioning
confidence: 99%